Behaviour under long-term loading of externally prestressed concrete beams. (1st April 2018) - Pisani, Marco Andrea
Highlights: Analysis of concrete beams externally prestressed and loaded by long-term loads. Solution of the system of Volterra integral equations by means of the Gauss quadrature formula. Alternative solution by making use of the AAEM algebrized method. Abstract: External posttensioning is a useful technique both for strengthening damaged beams, and for the construction of new girder bridges. In an externally posttensioned member, the prestressing tendons are located outside the cross section and connected to the structure by anchorages and deviators, that are the only points where compatibility occurs (at least in the direction orthogonal to the beam axis). This fact implies that a simply supported, externally prestressed beam is a redundant structure. Two numerical methods able to describe the time evolution of both the stress distribution and the displacements of a simply supported concrete beam externally prestressed are introduced and discussed. The distinction between them lies in the way they solve the Volterra integral that is involved in the solving system: one of them performs a numerical solution (almost exact) of this integral whereas the second one adopts an approximate solution. The example presented makes it possible to verify the precision of the approximate method when compared to the almost exact one.